Toxicity Study of 28-Day Subcutaneous Injection of Arctigenin in Beagle Dogs - Li, Jie; Lv, Yun-gang; Pan, Li-hong; Yao, Fang-fang; Peng, Tao; Tan, Yu-jun; Zhang, Gui-Min; Liu, Zhong; Yao, Jing-chun; Ren, Yu-shan (Frontiers in Pharmacology, 2019)
Abstract Our previous studies have investigated the systematic pharmacokinetic characteristics, biological activities, and toxicity of arctigenin. In this research, the potential toxicities of arctigenin in beagle dogs were investigated via repeated 28-day subcutaneous injections. Beagle dogs were randomly divided into control, vehicle (PEG), and arctigenin 6, 20, 60 mg/kg treated groups. The whole experimental period lasted 77 days, including adaptive period (35 days), drug exposure period (animals were treated with saline, PEG, or arctigenin for 28 consecutive days), and recovery period (14 days). 60 mg/kg arctigenin injection affected the lymphatic hematopoietic, digestive, urinary, cardiovascular, and all the impact on these tissues resulted in death in five dogs (three female and two male dogs); 20 mg/kg arctigenin injection resulted in toxic reactions of the lymphatic hematopoietic, digestive systems; and 6 mg/kg arctigenin and PEG injection did not lead to significant toxic reactions. Meanwhile, there were no sexual differences of drug exposure and accumulation when dogs underwent different dosages. As stated previously, the toxic target organs of arctigenin administration including lymphatic hematopoietic, digestive (liver and gallbladder), urinary (kidney), cardiovascular (heart) systems, and the no observed adverse effect level (NOAEL) of arctigenin is less than 6 mg/kg.